Stress‐induced tRNA cleavage and tiRNA generation in rat neuronal PC12 cells. Issue 5 (22nd April 2018) - Elkordy, Alaa; Mishima, Eikan; Niizuma, Kuniyasu; Akiyama, Yasutoshi; Fujimura, Miki; Tominaga, Teiji; Abe, Takaaki
Abstract: Transfer RNA (tRNA) plays a role in stress response programs involved in various pathological conditions including neurological diseases. Under cell stress conditions, intracellular tRNA is cleaved by a specific ribonuclease, angiogenin, generating tRNA‐derived fragments or tRNA‐derived stress‐induced RNA (tiRNA). Generated tiRNA contributes to the cell stress response and has potential cell protective effects. However, tiRNA generation under stress conditions in neuronal cells has not been fully elucidated. To examine angiogenin‐mediated tiRNA generation in neuronal cells, we used the rat neuronal cell line, PC12, in combination with analysis of SYBR staining and immuno‐northern blotting using anti‐1‐methyladenosine antibody, which specifically and sensitively detects tiRNA. Oxidative stress induced by arsenite and hydrogen peroxide caused tRNA cleavage and tiRNA generation in PC12 cells. We also demonstrated that oxygen‐glucose deprivation, which is an in vitro model of ischemic–reperfusion injury, induced tRNA cleavage and tiRNA generation. In these stress conditions, the amount of generated tiRNA was associated with the degree of morphological cell damage. Time course analysis indicated that generation of tiRNA was prior to severe cell damage and cell death. Angiogenin over‐expression did not influence the amount of tiRNA in normal culture conditions; however, it significantly increased tiRNA generation induced by cell stress conditions. Our findings show that angiogenin‐mediated tiRNA generation can be induced in neuronal cells by different cell stressors, including ischemia–reperfusion. Additionally, detection of tiRNA could be used as a potential cell damage marker in neuronal cells. Cover Image for this issue: doi:10.1111/jnc.14191 . Abstract : Cell stress conditions induce tRNA cleavage mediated by angiogenin, generating tRNA‐derived stress‐induced RNAs (tiRNAs), which have cell protective activities. We show that the angiogenin‐mediated tiRNAs generation can be induced in PC12 neuronal cells by different types of cell stresses including oxidative stress and ischemia–reperfusion. Additionally, detection of tiRNA could be used as a potential cell damage marker in neuronal cells. Cover Image for this issue: doi:10.1111/jnc.14191 .